Comparing Three Different Contrast Sensitivity Tests in Adults and in Children with and without Amblyopia - Ulrich, Kerstin; Palmowski-Wolfe, Anja (Klinische Monatsblätter für Augenheilkunde, 2019)
Background Tests of contrast sensitivity (CS) are not routinely performed in the clinic, although CS is reduced in many conditions, such as amblyopia or glaucoma. This may be due to perceived time constraints or unaffordability of equipment.Patients and Methods Monocular CS functions obtained with the FACT, CSV 1000E, and Lea Symbols were compared in 19 healthy subjects aged 24 – 78 years and 24 subjects aged 5 – 16 years, 9 of whom had amblyopia.Results CS functions could be obtained with all three tests. The tests were equally comfortable for young and adult patients, and took less than 5 minutes to perform (one eye). All measured CSs at 3, 6, 12, and 18 cycles per degree (cpd), but the FACT included 1.5 cpd.Linear mixed effect models were performed. While there was no significant difference at low spatial frequencies, the Lea CS test showed a ceiling effect in that range, while the FACT showed a floor effect at high spatial frequencies. CS in amblyopic children did not differ between the contralateral and the amblyopic eye. Overall, amblyopic eyes had lower CS values than the control eyes and CS did not correlate significantly to visual acuity at distance.Conclusion All three CS tests could be usefully applied in the clinic in adults as well as children over the age of 4 years. Only the CSV 1000E exhibited neither a ceiling nor a floor effect. This was also the fastest test. In children with amblyopia, CS testing offers additional information on visual function. In contrast to previous reports, we did not find that the CSV and FACT are interchangeable.
Keywords: CSV-1000E; 10M LEA SYMBOLS; Functional Acuity Contrast Test (FACT); contrast sensitivity